2012
DOI: 10.1007/s00018-012-1032-3
|View full text |Cite
|
Sign up to set email alerts
|

Tightrope act: autophagy in stem cell renewal, differentiation, proliferation, and aging

Abstract: Autophagy is a constitutive lysosomal catabolic pathway that degrades damaged organelles and protein aggregates. Stem cells are characterized by self-renewal, pluripotency, and quiescence; their long life span, limited capacity to dilute cellular waste and spent organelles due to quiescence, along with their requirement for remodeling in order to differentiate, all suggest that they require autophagy more than other cell types. Here, we review the current literature on the role of autophagy in embryonic and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 127 publications
4
90
0
1
Order By: Relevance
“…Our study showed that autophagic proteins play a critical role in regulating MSC survival under oxidative stress. Survival of MSCs after transplantation in damaged myocardium can be enhanced by autophagy-activating drugs (47). The process of autophagy could contribute to the engraftment of transplanted MSCs used in therapy, and lends itself to an application of prolonging survival of MSCs (47,48).…”
Section: Original Researchmentioning
confidence: 99%
“…Our study showed that autophagic proteins play a critical role in regulating MSC survival under oxidative stress. Survival of MSCs after transplantation in damaged myocardium can be enhanced by autophagy-activating drugs (47). The process of autophagy could contribute to the engraftment of transplanted MSCs used in therapy, and lends itself to an application of prolonging survival of MSCs (47,48).…”
Section: Original Researchmentioning
confidence: 99%
“…This catabolic process is indeed involved in the preservation of stem cell homeostasis and the maintenance of stemness property (reviewed in (Guan et al, 2013, Phadwal et al, 2013, Vessoni et al, 2012). Of note, the protein/organelle quality control operated by autophagy appears of particular relevance during periods of quiescence and/ or differentiation (Guan et al, 2013).…”
Section: Autophagy In the Physiology Of Cscsmentioning
confidence: 99%
“…Indeed, consideration of the available data suggests that the unique properties of stem cells (self-renewal, pluripotency, differentiation and quiescence) are dependent on the activation of the autophagic process. 12,13 First, the processes of self-renewal and differentiation both require a strict control of cellular remodeling that involves protein turnover and lysosomal degradation of organelles.…”
Section: Introductionmentioning
confidence: 99%